Pengembangan Media Pembelajaran Permainan Bola Besar Melalui Alat GaNeRi (Gawang, Net, Ring) untuk Peserta Didik Sekolah Menengah Pertama - Achmad Exvan Yusuf; Andry Akhiruyanto (Indonesian Journal for Physical Education and Sport, 2023)
The problem in this research is “How to Develompent of learning media for big ball games by using GaNeRi (Gawang, Net, Ring) tool for Junior High School student”. This research is a research and development or R&D. The research steps is a follows: 1) Potential and problems, 2) Data collection, 3) Product deign, 4) Design validation (1 big ball game expert and 2 learning expert), 5) Design revisions, 6) Small-scale trial (20 students), 7) Product revision, 8) Large-scale trials (40 students), 9) Product revisions, 10) Mass production that produce GaNeRi tool to facilitate the learning of the big ball games for Junior High School. The results of expert validation of the initial product of the study obtained an average percentage of 83% (very good), with some revisions such as the addition of several height variations on the net and ring. Then the product is tested on a small scale with an average percentage of 81,34% (very good). After that the product was revised by an expert and declared very usable. Then the produtc is tested on a large scale obtained average of 86,67% (very good). Conclusion of the research analysis, GaNeRi (gawang, net, ring) tool can be used as a means of learning big ball games in junior high school. Suggestions for physical education teachers are expected to be able to used this toolas a solution to overcome the problem of limited facilities and infrastructure for learning big ball games owned by schools.